Ekranisasi Novel Cintaku Untuk Si Mata Indah Karya Sri Rokhati ke Film Habibie & Ainun Karya Sutradara Faozan Rizal - Nafsi, Ghina; Hasanuddin WS, Hasanuddin WS; Zulfadhli, Zulfadhli (Jurnal Bahasa dan Sastra, 2014)
The purpose of this article is (a) to describe the story of episode novel Cintaku Untuk Si Mata Indah written by Sri Rokhati, (b) to describe the story of episode Habibie & Ainun movie director by Faozan Rizal, (c) to describe the similarity and differences the story of episode novel Cintaku Untuk Si Mata Indah with Habibie & Ainun movie. The data of this study is the story of episode novel Cintaku Untuk Si Mata Indah written by Sri Rokhati and Habibie & Ainun movie director by Faozan Rizal. Analysis technique is with ekranisasi theory. The finding of the study showed that the decreasing episode of the story novel Cintaku Untuk Si Mata Indah written by Sri Rokhati in Habibie & Ainun movie director by Faozan Rizal become 111 stories of episode. Additional of the story in Habibie & Ainun movie director by Faozan Rizal become 60 stories of episode. The change of variation event, character and background the story of episode in novel Cintaku Untuk Si Mata Indah written by Sri Rokhati and Habibie & Ainun movie director by Faozan Rizal become 10 stories of episode.